1990
DOI: 10.1103/physrevc.41.2118
|View full text |Cite
|
Sign up to set email alerts
|

Deformation effects in the compound nucleus decay using the spin-alignment method

Abstract: Alpha-particle energy spectra and angular distributions with respect to the estimated spin direction of residual nuclei have been measured in heavy-ion fusion reactions. The spin direction was determined for each event by measuring the y-ray angular correlation patterns using the Spin Spectrometer. Measurements were made for the compound nuclear systems " Sn*(94 MeV), " Sn (80 MeV), '"Nd (82 MeV), '~Yb (67 MeV), and ' Yb (135 MeV) at the indicated excitation energies as a function of the alpha-particle energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We will also integrate previous work done at lower energy (143 MeV) on the same reaction [1][2][3][4][5][6]7], where the evidence of a purely statistical gammadecay of nuclei formed in deep inelastic reactions and a strong non-statistical ):-emission in the quasi-elastic region was found.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…We will also integrate previous work done at lower energy (143 MeV) on the same reaction [1][2][3][4][5][6]7], where the evidence of a purely statistical gammadecay of nuclei formed in deep inelastic reactions and a strong non-statistical ):-emission in the quasi-elastic region was found.…”
Section: Introductionmentioning
confidence: 84%
“…Regarding the alpha-particles emitted with an energy lower than the Coulomb barrier (region I), in some papers [2,17] they were explained as originating from deformed fused nuclei. This effect cannot be neglected in our reaction (compound nucleus 92Mo) for which GDR deexcitation studies showed the presence of deformation [18].…”
Section: Alpha Particlementioning
confidence: 99%
See 2 more Smart Citations
“…Grover and Gilat first discussed this process in work published 25 years ago [5]. These early calculations, as well as more recent ones [7], predict that these "stretched" and "last chance" o. particles would be emitted &om states with lifetimes similar to the K-vacancy lifetime and therefore present an ideal application of the atoxnic clock xnethod. The predicted a-particle energies are low for these "last chance" particle emissions which, despite the angular moxnentum removed by the decay, tend to populate moderate to high spin states of the residue.…”
mentioning
confidence: 99%